2012
DOI: 10.1186/1747-597x-7-31
|View full text |Cite
|
Sign up to set email alerts
|

Screening and managing cannabis use: comparing GP’s and nurses’ knowledge, beliefs, and behavior

Abstract: BackgroundGeneral practitioners (GPs) and nurses are ideally placed to address the significant unmet demand for the treatment of cannabis-related problems given the numbers of people who regularly seek their care. The aim of this study was to evaluate differences between GPs and nurses’ perceived knowledge, beliefs, and behaviors toward cannabis use and its screening and management.MethodsThis study involved 161 nurses and 503 GPs who completed a survey distributed via conference satchels to delegates of Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…As far as drug and alcohol addicts are concerned, many physicians and nurses took on a reluctant behavior in approaching these patients, fearing they could lie about their use of substances [27,30,31]. The score of fear in this study indicates that HCWs are still scared of HIV patients’ and drug users’ behavior.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As far as drug and alcohol addicts are concerned, many physicians and nurses took on a reluctant behavior in approaching these patients, fearing they could lie about their use of substances [27,30,31]. The score of fear in this study indicates that HCWs are still scared of HIV patients’ and drug users’ behavior.…”
Section: Discussionmentioning
confidence: 81%
“…In the same way, several studies have shown that the competence of physicians and nurses in the care and prevention of alcohol and drug addiction is strategically important [27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…As specialist providers are not commonly sought, it is of interest to determine GPs' ability to treat cannabis use. Most notably, GPs frequently report time pressures and a need to address more important issues than cannabis use (40), as well as difficulties in addressing the issue (41).…”
Section: Cannabis Treatment In the Communitymentioning
confidence: 99%
“…Em um desses estudos que incluiu médicos e enfermeiros, os resultados mostraram que menos de 1/3 dos médicos generalistas considerava suas habilidades para lidar com dependentes de maconha aceitáveis. Apesar de parecer baixa, essa porcentagem foi ainda menor entre enfermeiros 23 . Uma ampla revisão publicada em 2013 sobre o tema também apresenta mais dados sobre enfermeiros e poucos sobre psicólogos, terapeutas ocupacionais e assistentes sociais 24 .…”
Section: Discussionunclassified